A Parasitoid Wasp Cotesia congregata (Say) (Insecta: Hymenoptera: Braconidae) - Christopher D. Crockett; Andrea Lucky; Oscar E. Liburd; Karen M. Kester (EDIS)
This species of Cotesia has been widely used as a model system in insect physiology. It has also been used to examine insect learning in host-parasitoid-plant interactions. It is an important natural enemy of the tobacco hornworm, a detrimental pest species that feeds on many plants in the Solanaceae (tobacco, pepper, tomato, etc.) family. This 5-page fact sheet was written by Christopher D. Crockett, Andrea Lucky, Oscar E. Liburd, and Karen M. Kester, and published by the UF Department of Entomology and Nematology, July 2014.